Axiological and Ideological Meaning of the Constitutional Reform that Began in 2020 in Russia - S. N. Baburin (Теоретическая и прикладная юриспруденция)
The article discusses the issues of constructing a multipolar world, which can successfully exist only in conditions of harmony of the spiritual meanings of the legal traditions of its constituent peoples. The decisive role of spiritual and moral values that underlie the civilizational cultural and historical self-identification of existing states, and the need to find ways to build moral states of various civilizations are argued. International development can only be built on a solid legal basis that combines the organic constitutional development of national states and the formation of international law on the traditional spiritual and moral principles.